Occupational segregation and the gender wage gap in private- and public-sector employment: a distributional analysis - Juan D. Barón; Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2008)
We use HILDA data from 2001 - 2006 to analyse the source of the gender wage gap across public- and private-sector wage distributions in Australia. We are particularly interested in the role of gender segregation within sector-specific occupations in explaining relative wages. We find that, irrespective of labour market sector, the gender wage gap among low-paid, Australian workers is more than explained by differences in wage-related characteristics. The gender wage gap among high-wage workers, however, is largely unexplained in both sectors suggesting that glass ceilings (rather than sticky floors) may be prevalent. Gender differences in employment across occupations advantage (rather than disadvantage) all women except those in high-paid, private-sector jobs, while disparity in labour market experience plays a much more important role in explaining relative private-sector wages. Finally, disparity in educational qualifications and demographic characteristics are generally unimportant in explaining the gender wage gap.
urn:nbn:de:101:1-2008062742
Keywords: J31; 330; Gender wage gap; occupational segregation; private and public sector employment; Lohndifferenzierung; Arbeitsmarktdiskriminierung; Geschlechterdiskriminierung; Beruf; Australien